Fostering Equitable Disciplinary Literacy Practices - Heather Waymouth; Kathleen A. Hinchman (Education Sciences)
A burgeoning amount of research has recently been published to foster equitable disciplinary literacy practices in secondary schools. The literature review included in this paper examined this recent scholarship with a multistep qualitative analysis of 31 studies published between 2019 and 2024 to explore how these studies conceptualized and actualized attention to equity in discipline literacy instruction. The analysis revealed three overlapping themes reflecting the studies’ conceptualizations of how to address equity with disciplinary literacy. These included equity as access to disciplinary instruction, equity as scaffolding literacy for disciplinary learning, and equity as engaging in locally and culturally relevant inquiry. The Results Section summarizes how the studies reviewed addressed these themes. Studies situated disciplinary literacy in many types of instructional contexts, including subject-area classrooms and segregated settings for students with learning differences, suggesting a notion of equity as making disciplinary literacy instruction available to all students. Most disciplinary literacy instruction supported students’ reading, discussion, writing, and argumentation to report on results of disciplinary study, suggesting that equitable disciplinary literacy instruction was provided as needed support with a focus on students engaging in disciplinary studies. A few studies addressed, instead, school and classroom literacy culture or a focus on achievement that seemed to inhibit students’ ability to benefit from disciplinary literacy efforts. More than half of the studies reviewed focused on teachers’ orchestration of compelling, culturally relevant student inquiry, suggesting equitable disciplinary literacy instruction as needing to be relevant to students. Only a few studies delineated what such instruction would need to look like to build student independence over time and to include inquiry into multiple perspectives toward key disciplinary ideas. The paper ends with a summary, critique, and conclusion that encourages further long-term studies involving the schoolwide use of equitable disciplinary literacy approaches.